The role of internal auditors in preventing financial fraud in the Republic of Serbia - Jeremić Nebojša; Jakovljević Nemanja (Trendovi u Poslovanju)
Financial fraud poses a significant threat to the stability and integrity of financial systems around the world. The Republic of Serbia, as an economy in dynamic development, is no exception to this challenge. This research paper investigates the key role of the profession of internal auditors in the fight against financial fraud in the Republic of Serbia. By exploring the practices and challenges faced by internal auditors, this paper aims to provide valuable insights and recommendations to strengthen the effectiveness of internal audit functions in detecting and preventing financial fraud. The importance of internal audit as a vital component of corporate governance and risk management was emphasized through a review of relevant literature and consideration of various activities of internal auditors and their role in preventing financial fraud. Internal auditors play a key role in assessing and monitoring internal controls, identifying vulnerabilities and making recommendations to mitigate fraud risk. Examining the legal and regulatory framework that regulates internal audits in the Republic of Serbia, the importance of implementing a strong control environment and effective monitoring mechanisms in preventing financial fraud is highlighted. The paper's conclusions highlight the specific challenges internal auditors face in the Republic of Serbia in preventing financial fraud, such as resource limitations, limited independence and insufficient awareness of fraud. The findings and recommendations presented in the paper can serve as a valuable resource for policymakers, regulatory bodies and organizations seeking to strengthen their financial fraud defense mechanisms and their internal audit function.